Thinking English Literature and Criticism under the Transmodern Paradigm. Issue 3 (December 2017) - Onega, Susana
Abstract : Starting from a consideration of the contrasting views on the reading and teaching of English literature held by Ranjan Ghosh and J. Hillis Miller in Thinking Literature across Continents, the essay draws a parallel between Ghosh's Eastern definition of literature through it 'uselessness' and that of the Western visionary tradition stemming from Plato and further developed by the Romantic poets as a counter-textual movement against Enlightenment rationalism. From this, it goes on to relate the value of literature to the mimetic function and to argue that, although there is a general impression that we are currently living in a post-literary age, literature is in fact developing a plethora of new forms, genres and modes that proves its intrinsic capacity to adapt to the changing demands of the successive dominant paradigms. It concludes by suggesting that this adaptability of literature is paralleled by a similar evolution and diversification of critical approaches, and that at present there are signs of a worldwide change of sensibility heralding a paradigm shift from postmodernity to transmodernity.